The Development of Learning Questioning-answering Model with Artificial Intelligence to Enhance Entrepreneurial Mindsets on The Basis of Phitsanulok Soft Power for Undergraduate Students - Yuangsoi, Pichayapha; Meesuwan, Wiwat (Dhammathas Academic Journal, 2025)
The objectives for this research were: 1) to analyze the components of a learning Questioning-Answering Model with Artificial Intelligence to enhance Entrepreneurial Mindsets based on Phitsanulok Soft power, 2) to develop and validate the quality of the learning model, 3) to study the effects of implementing the learning model, with the following sub-objectives: (1) to compare enhance Entrepreneurial Mindsets after the learning with the criteria of 80%, (2) to study students’ satisfaction with the learning activities based on the model and 4) to certify the learning model by experts The samples were 289 students who enroll in the second semester in 2024 who registered to study in the course 001226 Digital Ways Group 1. The data were collected by employing 1) learning model, 2) evaluation forms, and 3) a Satisfaction questionnaire and analyzed by using percentage, mean, standard deviation, and One sample t-test. The results revealed that: 1. The developed model consisted of 4 components: 1. Principles 2. Objectives 3. The learning process consisted of six stages: (1)Lesson introduction, (2) Reading and media viewing, (3) Planning and formulating group questions, (4) Socratic dialogue with AI, (5) Reviewing and Summarizing, (6) Creative activities, and 4. Measurement and evaluation. 2. The learning model was designed based on the framework of Joyce, Weil, and Calhoun. Upon expert evaluation, the model was deemed highly appropriate. 3. Results of using the learning model: 1) Students’ understanding of the entrepreneurial conceptual framework after learning through the model exceeded the 80%, with statistical significance at the .01 level. 2) Students expressed high overall satisfaction with the learning activities based on the model. 4. Expert certification confirmed that the developed learning model was suitable for use in teaching and learning management.